2021
DOI: 10.1002/cpp.2549
|View full text |Cite
|
Sign up to set email alerts
|

Group eye movement desensitization and reprocessing interventions in adults and children: A systematic review of randomized and nonrandomized trials

Abstract: This review systematically synthesized existing literature on group protocols of eye movement desensitization and reprocessing (EMDR) therapy for treating a range of mental health difficulties in adults and children. We conducted database searches on PsychINFO, EMBASE, MEDLINE, Web of Science, The Cochrane Library and Francine Shapiro Library up to May 2020, using PRISMA guidelines. Studies were included if they used at least one standardized outcome measure, if they present a quantitative data on the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 67 publications
(123 reference statements)
1
26
1
Order By: Relevance
“…More importantly, group EMDR may represent an effective strategy as an early intervention and prevention of the development of psychological disorders in the long term following situations of acute stress [102]. Interestingly, miRNA-29a was identified as a response predictor for EMDR integrative effects [103] (while a mindfulness intervention [104] was found to improve cognitive function [105] by increasing the neuronal expression of miRNA-29c [106]), so a group EMDR intervention may represent an effective strategy to promote integration in clinical [52] and non-clinical individuals [107].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, group EMDR may represent an effective strategy as an early intervention and prevention of the development of psychological disorders in the long term following situations of acute stress [102]. Interestingly, miRNA-29a was identified as a response predictor for EMDR integrative effects [103] (while a mindfulness intervention [104] was found to improve cognitive function [105] by increasing the neuronal expression of miRNA-29c [106]), so a group EMDR intervention may represent an effective strategy to promote integration in clinical [52] and non-clinical individuals [107].…”
Section: Discussionmentioning
confidence: 99%
“…Group EMDR therapy is a well-proven form of treatment for traumatized children and adolescents [51][52][53][54]. To our knowledge, no study to date has evaluated the possible differential simultaneous effects of a group EMDR intervention on narrative complexity, specificity of autobiographical memories, event coding, SUD, and VoC in children aged 9-11 years.…”
Section: Introductionmentioning
confidence: 99%
“…Intervention modality was a source of significant difference between group and individual EMDR on PTSD symptoms, showing that EMDR, while effective in both modalities, had larger effects when applied individually than in groups. This finding needs to be explored in future studies as recent reviews have highlighted the efficacy of group EMDR with both adults and children (Kaptan, Dursun, Knowles, Husain, & Varese, 2021; Rafieifar & Macgowan, 2022). The subgroup finding in this study may be complicated by differences in the levels of PTSD symptoms or ages of samples in the included research.…”
Section: Discussion and Applications To Practicementioning
confidence: 97%
“…EMDR group therapy is an efficacious intervention, typically producing large effect sizes. Although the methodology in most studies has been poor (Kaptan et al, 2021), the acceptability of the treatment is shown by widespread use around the world. Originally developed for rapid use in disaster settings and recent traumas, EMDR group treatment is now being successfully used for historical traumas (e.g., with refugees) and for traumas which have "ongoing" triggers or traumatic stressors (e.g., patients with cancer).…”
Section: Emdr Group Treatmentsmentioning
confidence: 99%